Monitoring the Effects of Hemicellulase on the Different Proofing Stages of Wheat Aleurone-Rich Bread Dough and Bread Quality - Boyu Tian; Chenxia Zhou; Dongxiao Li; Jiawei Pei; Ailiang Guo; Shuang Liu; Huijing Li (Foods, 2021)
This study investigated the effects of a hemicellulase dosage (20, 40, and 60 mg kg−1 of flour) on the bread quality and rheological properties of wheat aleurone-rich flour. The results showed that hemicellulase could soften dough and improve extensibility. At the optimum hemicellulase dosage (40 mg kg−1 of flour), the bread specific volume increased by 40.91% and firmness of breadcrumb decreased by 104.57% compared to those of the control. Intermolecular forces indicated that the gluten network during the proofing was mainly strengthened via disulfide bonds, hydrophobic interactions, and hydrogen bonds but not through ionic bonds after hemicellulase addition. Fourier infrared spectroscopy indicated that the hydrolytic activity of hemicellulase catalyzed the transition from α-helix to β-sheet, which verified that viscoelasticity of gluten was enhanced at a dosage of 40 mg kg−1 of flour. These results suggested that hydrolyzation of hemicellulase contributed to the structural of gluten changes, thereby improving the quality of wheat aleurone-rich bread.